MR and CT characteristics of gangliocytoma: a rare cause of epilepsy in children. - Altman, N R (American Journal of Neuroradiology, 1988)
Three children were examined who had surgery to remove gangliocytomas in order to control seizures that were refractory to medical therapy. The CT characteristics of gangliocytomas are those of a hyperdense lesion that does not demonstrate contrast enhancement. The MR findings show a region of mixed signal intensity on T1-weighted and proton-density images, and decreased signal intensity on T2-weighted images. Little mass effect, if any, is seen with these lesions.